Giovanni Pettinato, The Archives of Ebla - An Empire lnscribed in Clay, with an afterword by Michael Dahood, S.J., Doubleday & Co. Inc. Garden City, New York, 1981. - Silva Castillo, Jorge (Estudios de Asia y África, 1984)
-